Development of an online module in nutrition - Benito, Marilyn A. (2001)
This project is a development research that followed four phases in developing an educational product. The first phase, Initial Product Planning, included a needs assessment survey among students and teachers of nutrition. A key informant interview among teachers and a quick survey using a self-administered questionnaire, was done to collect information on the needs and problems of both groups, in terms of teaching, and in learning, the essential nutrients. The second phase, the Preliminary Development phase, is the preparation of the self-instructional material on the essential nutrients: its functions, sources, deficiency or excess, requirements or allowances. The third phase, the Educational Product Development, is the preparation and implementation of the nutrition material through online mode. This was done through web site and web pages creation, registration and upload to the Internet. The fourth phase, the Qualitative Evaluation phase, included a field testing of the developed online nutrition module among students and teachers of nutrition. The online module's accessibility, presentation and content were tests. Likewise, recommendations for improvement were elicited through the use of a self-administered questionnaire. Three hundred and seventy-nine (379) students and five (5) teachers participated in the first phase, while 109 students and 17 teachers participated in the fourth phase. The results of the study showed that, although students are satisfied with the way nutrition courses were handled, there are still problems and issues that needs to be addressed. Identified problem areas in learning nutrition concepts was on the scope of subject itself and the teaching methodologies and strategies teachers use in classroom teaching. This suggests that teachers need to address such problems to achieve meaningful learning experiences among learners of nutrition. The study also implies that the use of computer-assisted instruction, may be a potential method for enhancing nutrition education. As computers become an integral component of the student's life, so it can be a means of learning nutrition concepts as well. Finally the study showed that online learning mode is useful, feasible and practical among students and teachers of nutrition. As the respondents find the module fun, and interesting way to learn the essential nutrients, points for improvements were given.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Nutrition -- Study and teaching